Microscopic Features of Central Caseous Necrosis in Tuberculosis Lymphadenitis Patients: The Relationship with Lymphocyte Density - Rafa Nabila Haifa; Humairah Medina Liza Lubis (Buletin Farmatera, 2023)
Tuberculosis lymphadenitis (TBLN) is the most common extra pulmonary TB (EPTB) case in the world with a range of 30-40% of all EPTB cases. When the body's immune system cannot kill the pathogen, the body will try to contain the pathogen (granuloma). The outer portion of the granuloma becomes calcified and the cells in the center undergo necrosis. The formation of central necrosis is associated with the emergence of cellular hypersensitivity with the features of local accumulation of macrophages and lymphocytes. The current study aimed to determine the relationship between the microscopic features of central caseous necrosis with lymphocyte density in patients with tuberculous lymphadenitis. Thirty histopathological slides of TBLN patients were observed under a microscope to see the features of central caseous necrosis and assess the lymphocyte density with the results assessed based on the cutoff point of the median of all lymphocyte mean values. Based on the microscopic examination, 25 samples of central caseous necrosis were found and the other 5 samples were not found to have caseous necrosis. Twenty-six patients had low lymphocyte density, and 4 patients had high lymphocyte density. The results of the Fisher Exact test obtained p = 0.009. There is a significant relationship between the features of central caseous necrosis and lymphocyte density in patients with TBLN.